精神科コンサルテーション・リエゾンチームにおける各職種の役割構築に向けたパイロットスタディ - 山内 典子; 安田 妙子; 小林 清香; 異儀田 はづき; 筒井 順子; 西村 勝治; 田中 美恵子 (Japanese Journal of General Hospital Psychiatry, 2013)
After reviewing 731 cases in which the CLT at Tokyo Women's Medical University Hospital had intervened, we identified differences among those cases with intervention by single function care providers and a team deploying multiple functions. From the 731 cases, we further reviewed the details and structures of 63 cases that involved the psychiatric liaison nurses and clinical psychotherapists. Patients with sleep disorders were treated by physicians; patients with adjustment disorders were treated by the psychiatric liaison nurses; more patients with impaired psychic functions (e.g., deliria) before transplant or with Axis IV were treated by the multiple functions teams than those treated by single function care providers. By emphasizing the educational and emotional support to other medical care providers, the psychiatric liaison nurses and clinical psychotherapists have been promoting cooperation both within and outside the team. Characteristically, the liaison nurses mediated conflicts within the nursing team, assessed self-care and provided assurance and sympathy through active listening; the latter assessed the psychological state of the patients by utilizing objective tools and providing the patients demonstrating severe psychopathological disorders with systematic psychotherapy. It is possible for care providers to offer treatment intervention from an interdisciplinary point of view, by indexing the psychological problems according to medical and psychosocial complexity and the difficulties in performing the jobs of the medical care personnel. 東京女子医科大学病院の精神科CLT が介入した731件の事例に関し，単独の職種による介入とチームによる介入の差異を概観したうえで，リエゾンナース・臨床心理士が介入した63事例の内容と構造を示した。睡眠障害は医師，適応障害はリエゾンナースにより，また，せん妄など移植前の精神機能評価，Ⅳ軸のある患者は単独の職種よりもチームで多く介入していた。リエゾンナース・臨床心理士は，医療者への教育的・情緒的支援にも重きを置き，チームの内外で連携を促進していた。 各特性として，前者は看護チーム内の葛藤の調整，セルフケアの査定，適応障害患者への積極的傾聴を中心とした保証，後者は客観的ツールも加えた精神状態の査定，精神病理の重い患者への体系的な心理療法を担っていた。医学的・心理社会的複雑さからみる精神的問題とともに，医療者の対応の困難度を役割分担の指標とすることにより，多角的な見方，多方面からの介入が可能となると考えた。